Prevalence of alcohol and drug consumption and knowledge of drug/alcohol-related sexual assaults among Italian adolescents - Antonio Villa; Alessia Fazio; Anna Esposito (Journal of Health and Social Sciences)
Introduction: Alcohol is the most widely used substance among adolescents, exceeding the use of tobacco and illicit drugs. The study aims at investigating the prevalence of alcohol and drug use and prevalence and knowledge of Drug Facilitated Sexual Assault (DFSA) among Italian adolescents. Methods: The study population was a sample of 512 students of secondary education (high school) from 3 public schools in Milan, Italy. Two hundred and fourty-nine boys and 263 girls aged 15 to 21 years old (M = 16.2, SD = 2.1) answered a specially structured anonymous questionnaire. Results: Recent problem drinking (‘every day’ or ‘once a week’) was reported from 9% (‘wine’) up to 28% (‘beer’) of students. Cannabis and rave drugs usage (ranged from ‘every day’ to ‘once only in a while’) were reported by up to 38% (‘cannabis’) and 2% (‘rave drugs’) of students. Beer was the most popular type of alcoholic beverage (81%) with respect to wine (62%) and hard liquor (66%). Only a small percentage of participants stated that they were informed about the possible addiction to alcohol (5%) and its negative social consequences (3%). Nevertheless, almost all the students (92%) declared that alcohol consumption was less dangerous than other psychoactive substances. Finally, most students stated to know DFSA phenomenon (77%) and were victims or witness (13%) of a DFSA event. Conclusion: Psychoactive substances consumption remains a serious problem among Italian adolescents. For a successful alcohol strategy there is a need to implement preventive measures and counseling approaches in school. Increasing the knowledge of the negative effects of alcohol/drugs use might also lead to a better prevention of the DFSA phenomenon.